Improved glycemic control by acarbose therapy in hypertensive diabetic patients: effects on blood pressure and hormonal parameters - P. Rosenbaum; R.B. Peres; M.T. Zanella; S.R.G. Ferreira (Brazilian Journal of Medical and Biological Research, 2002)
A double-blind, randomized, placebo-controlled study was carried out on 44 hypertensive type 2 diabetic subjects previously treated by diet associated or not with sulfonylurea to assess the effects of acarbose-induced glycemic control on blood pressure (BP) and hormonal parameters. Before randomization and after a 22-week treatment period (100 to 300 mg/day), the subjects were submitted to a standard meal test and to 24-h ambulatory BP monitoring (ABPM) and had plasma glucose, glycosylated hemoglobin, lipid profile, insulin, proinsulin and leptin levels determined. Weight loss was found only in the acarbose-treated group (75.1 ± 11.6 to 73.1 ± 11.6 kg, P<0.01). Glycosylated hemoglobin decreased only in the acarbose group (6.4 ± 1.7 to 5.6 ± 1.9%, P<0.05). Fasting proinsulin decreased only in the acarbose group (23.4 ± 19.3 to 14.3 ± 13.6 pmol/l, P<0.05), while leptin decreased in both (placebo group: 26.3 ± 6.1 to 23.3 ± 9.4 and acarbose group: 25.0 ± 5.5 to 22.7 ± 7.9 ng/ml, P<0.05). When the subset of acarbose-treated patients who improved glycemic control was considered, significant reductions in diurnal systolic, diastolic and mean BP (102.3 ± 6.0 to 99.0 ± 6.6 mmHg, P<0.05) were found. Acarbose monotherapy or combined with sulfonylurea was effective in improving glycemic control in hypertensive diabetic patients. Acarbose-induced improvement in metabolic control may reduce BP in these patients. Our data did not suggest a direct action of acarbose on insulin resistance or leptin levels.